Effects of fifth day (D5) or sixth day (D6) frozen–thawed blastocysts on neonatal outcomes. Issue 5 (29th June 2016) - Wang, Xue; Zhen, Jingran; Sun, Zhengyi; Yu, Qi; Deng, Chengyan; Zhou, Yuanzheng; Wang, Hanbi; He, Fangfang
Summary: This study aimed to compare the neonatal outcomes of transplanted fifth day (D5) or sixth day (D6) frozen–thawed blastocysts, aiming to provide guidance when choosing blastocyst recovery methods. The clinical data of 1109 patients that were performed for recovered blastocyst transplantation, as well as the data of 515 patients who had already delivered were analyzed retrospectively. The patients were divided into single- or twins-birth groups according to blastocyst formation time (D5 or D6) and the number of fetus(es). The implantation rate, clinical pregnancy rate and live birth rate of the D5 group were all significantly higher than those in the D6 group ( P < 0.05), and the biochemical pregnancy rate in the D5 group was significantly lower than that in the D6 group ( P = 0.049). Other factors, including birth weight, birth length, incidence of low birth weight and sex ratio, differed between the D5 and D6 groups, but the difference was not statistically significant ( P > 0.05). In conclusion, the implantation rate, clinical pregnancy rate and live birth rate in the D5 group were all significantly higher than that in the D6 group. The birth weight at D6 was prone to be heavier no matter the birth group, and the sex ratio in the D5 group was higher than that at D6, the difference in neonatal outcomes between the two groups was not statistically significant.